2018
DOI: 10.5194/angeo-36-761-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of accelerometer data calibration methods used in thermospheric neutral density estimation

Abstract: Abstract. Ultra-sensitive space-borne accelerometers on board of low Earth orbit (LEO) satellites are used to measure non-gravitational forces acting on the surface of these satellites. These forces consist of the Earth radiation pressure, the solar radiation pressure and the atmospheric drag, where the first two are caused by the radiation emitted from the Earth and the Sun, respectively, and the latter is related to the thermospheric density. On-board accelerometer measurements contain systematic errors, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…We here speculate that the mean difference in the along-track direction is caused by a mean bias in the modeled drag acceleration. In the cross-track direction, the mean differences between modeled and calibrated accelerations according to Vielberg et al (2018) are about 4 × 10 −10 m/s 2 , which is about three orders of magnitude smaller than in the comparison above. Interestingly, the mean difference between modeled and our calibrated accelerations increases by about one order of magnitude when adding the instantaneous thermal reradiation.…”
Section: Consisting Of Constant Scale Factors and Biases Frommentioning
confidence: 55%
See 4 more Smart Citations
“…We here speculate that the mean difference in the along-track direction is caused by a mean bias in the modeled drag acceleration. In the cross-track direction, the mean differences between modeled and calibrated accelerations according to Vielberg et al (2018) are about 4 × 10 −10 m/s 2 , which is about three orders of magnitude smaller than in the comparison above. Interestingly, the mean difference between modeled and our calibrated accelerations increases by about one order of magnitude when adding the instantaneous thermal reradiation.…”
Section: Consisting Of Constant Scale Factors and Biases Frommentioning
confidence: 55%
“…is here computed for different model extensions RMSD 2 with respect to the standard model RMSD 1 , i.e., the positive results mean that accelerations from the extended model version are closer to calibrated accelerations than the standard model. In the comparison against calibrated accelerations from Vielberg et al (2018), we found that extended ERP and SRP accelerations have no impact on the modeled along-track acceleration because here the drag dominates. Interestingly, visible and infrared fluxes in the SRP model bring the modeled cross-track accelerations about 5.5% closer to calibrated observations from Vielberg et al (2018).…”
Section: Consisting Of Constant Scale Factors and Biases Frommentioning
confidence: 91%
See 3 more Smart Citations